The Effect of Early and Late Weaning of Awassi Ewe on the Milk Characteristics - ZinAlabidin, Mohammed M.; Albayati, Husham Jaafar Musa; Hassan, Shahla F.; Nadhim, Aya A.; Shaker, Ahmed S. (jurnal makanan tropis dan teknologi agroindustri, 2026)
The objective of the present study was to assess the impact of early and late weaning on ewe performance, lamb postnatal growth, hormonal status and milk composition in Awassi ewes over a 30 days separation period at Animal Production Farm, College of Agriculture, Kirkuk University. Fifteen healthy, mature ewes were randomly assigned into two groups according to the weaning age: EWG (early weaning, }) at 60 days or LWG (late weaning, at 90 days. All the groups were kept in the same conditions of environment and nutrition. Body weights were determined for ewes and lambs at the start and end of the experiment, and blood and milk samples were obtained for hormonal and compositional analyses, respectively. The results of ANOVA showed that the short and the long weaning strategy had no effect on ewe body weight. Nevertheless, final weights of lambs in the EWG were significantly higher than in the LWG (P≤0.05), indicating better growth in early weaned lambs. Hormonal results Serum PRL levels were significantly raised in the EWG; serum E2, P, LH, and FSH levels did not significantly differ between groups. Milk composition analysis indicated that early weaning significantly increased milk fat, whereas protein, lactose, and solid non-fat of milk did not differ between groups. Results of correlation analysis showed high positive correlations between milk components, most notably between solid non-fat, protein, and lactose. These results indicated that early weaning improved lamb growth performance, increased milk fat with no detrimental effects on ewe health or reproductive hormone balance. The results reinforce the early weaning as a pragmatic alternative for enhancing efficiency in sheep production systems.